Psicoterapia psicanalítica com idosos: uma reflexão necessária - Marinho, Juliana de Castro Tourinho (2021)
This work aimed to understand how elderly patients are being treated, perceived, seen and heard by eight psychologists with a psychoanalytical theoretical basis grounded in Winnicott. It is a qualitative research, in which the psychoanalytical method was used to analyze the interviews conducted with each psychologist. As a research instrument, the semi-open questionnaire was used. After a bibliographic search, which sought to understand how the elderly person was seen by the different societies that existed in the past and how it is possibly seen by contemporary society, as well as subjective aspects related to the aging process and entry into old age; one analysis was performed for each interview and two subsequent analyzes, in which four interviews were grouped in each. The final discussion included five main points that emerged predominantly from the analyzes carried out. They are: The old age that dwells in me x The old age that shows itself to the other, which addressed otherness issues that permeate aging; Real death x death in life, which pointed out the subjective impact caused by psychologists when they face death in the care of the elderly; Forgiveness, an issue that revealed the sensitivity of psychotherapists to perceive the path to be taken in psychotherapy with elderly patients who apprehend themselves to be close to death, in the sense of reframing purely subjective issues in the life that has already passed; Studies and operation in the field of prevention, a topic of discussion that pointed to the need to debate and study more about the possibility of psychotherapeutic work with the elderly that would walk towards prevention and, finally; the last topic of discussion that emerged from the analysis: The lack of demand and the very few search of the elderly for psychotherapy, a topic that launched a challenge to contemporary psychotherapists, in the sense of welcoming the time of the elderly and their questions, working in order to produce demand for this population, acting in the opposite direction of the functioning currently found in the social environment.